The material removal and the nanometric surface characteristics formation mechanism of TiC/Ni cermet in ultra-precision grinding. (April 2021) - Zhu, Yandan; Zhang, Quanli; Zhao, Qingliang; To, Suet
Abstract: In this paper, the material removal mechanism of TiC/Ni cermet is firstly investigated based on the analysis of the nano-indentation and the diamond scratching test, and the grinding induced surface damage mechanics is then explored according to the surface topography, the surface morphology and the material microstructure analysis. The results show that the material removal experienced plastic deformation, plowing and fracture under the dynamic scratching process, where the material microstructure plays a determinant role on the obtained surface characteristics of the TiC/Ni cermet. To achieve a smooth surface and ductile material removal by the ultra-precision grinding process, a group of the machining parameters is selected to reveal the formed nanometric surface characteristics, where the dislodgement of the hard TiC particles and the surface relief formation were induced by the varied material removal rate between the binding phases and the TiC hard particle under the scratching of the diamond grits. In addition, the preferred TiC (200) crystalline plane in the ground surface layer appears for the interface fracture between the TiC grains and the rim structure, while the Ni (111) crystalline plane shows a preferred growth for the extrusion in the subsurface deformed layer. Highlights: The typical material removal modes of TiC based cermet are identified. The randomly distributed micro-pits formed by surface fracture and material dislodgement. The preferred crystalline orientation for both TiC and Ni are induced by the grinding process.